Zearalenone and 17 β-estradiol induced damages in male rats reproduction potential; evidence for ERα and ERβ receptors expression and steroidogenesis. (15th September 2016) - Adibnia, Elmira; Razi, Mazdak; Malekinejad, Hassan
Abstract: The estrogen receptors (ERs)-dependent effects of Zearalenone (ZEA) on structure and function of the testis as well as sperm parameters were compared with 17-β estradiol as endogenous substance. For this purpose, 30 mature male rats were assigned into five groups as; control (appropriate volume of normal saline, i. p.), ZEA-received (1, 2 and 4 mg/kg, b. w., i. p.) and 17 β-estradiol (E2 )-received (appropriate dose of 0.1 mg/kg, i. p.). Following 28 days, the mRNA levels of estrogen receptor alpha (ERα) and estrogen receptor beta (ERβ) in the testis and sperms and the expression of them at protein levels in testicles were estimated. Mitochondrial content of germinal epithelium, Leydig cells steroid foci, sperm quality parameters and serum level of testosterone were assessed. Fluorescent techniques were used for analyzing apoptosis and mRNA damage in necrotic cells. ZEA reduced the mRNA and protein levels of ERα in testicles while up-regulated the ERβ expression. The mRNA level of ERα decreased in sperms of ZEA and E2 -received animals. No remarkable changes were found for ERβ expression in sperms from ZEA and E2 -received animals. ZEA reduced the Leydig cells steroidogenesis, mitochondrial content of germinal cells and elevated cellular apoptosis and necrosis dose-dependently. E2 reduced the testosterone concentration, enhanced the apoptosis and reduced sperm quality. Our data suggest that ZEA-induced detrimental effects in the structure and function of testis, may attribute to changing the ERs expression at mRNA and translational level. Graphical abstract: Highlights: ZEA reduces ERα and up-regulates ERβ expressions in testicular tissue. ZEA by influencing ERα expression affects sperm quality parameters. ZEA reduces the mitochondrial content, which in turn promotes apoptotic and necrotic pathways. E2 affects testicular endocrine status and ERα expression at sperm level. Both E2 and ZEA do not change the ERβ mRNA level in sperms.